Which Factors Contribute to Innovative Performance? A Case Study Applied to the Food and Beverage Industry 2022
DOI: 10.37247/pagen2ed.2.22.16
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Revealed the Freezing Tolerance Signaling Events in Winter Rapeseed (Brassica rapa L.)

Abstract: Data Availability Statement:The raw transcriptome reads have been deposited into the NCBI Short Read Archive (SRA) under accession number PRJNA782399. Conflicts of Interest:The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest.Author Contributions: WW and YW conceived and designed this study. YW, HY, JS, YD, PX, and JH performed the experiments. WW, LD, GW and SZ analyzed the data. YW performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…According to various transcriptome data, several genes and transcription factors play an essential role in photosynthesis, plant hormone signal transduction, and mitogen-activated protein kinase signal cascades under different abiotic stresses ( Li et al., 2019 ; Ermilova, 2020 ; Ritonga and Chen, 2020 ; Aslam et al., 2022 ). In this study, the annotation of Gene Ontology and KEGG enrichment analysis demonstrated that low temperatures regulated the expression of several DEGs in the photosynthetic pathway of photosynthesis ( Wu et al., 2020 ) and activated numerous DEGs and transcription factors in signal transduction pathways ( Wang et al., 2018 ; Wu, 2022 ) under shade and no-shade control plants in November and December, respectively.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…According to various transcriptome data, several genes and transcription factors play an essential role in photosynthesis, plant hormone signal transduction, and mitogen-activated protein kinase signal cascades under different abiotic stresses ( Li et al., 2019 ; Ermilova, 2020 ; Ritonga and Chen, 2020 ; Aslam et al., 2022 ). In this study, the annotation of Gene Ontology and KEGG enrichment analysis demonstrated that low temperatures regulated the expression of several DEGs in the photosynthetic pathway of photosynthesis ( Wu et al., 2020 ) and activated numerous DEGs and transcription factors in signal transduction pathways ( Wang et al., 2018 ; Wu, 2022 ) under shade and no-shade control plants in November and December, respectively.…”
Section: Discussionmentioning
confidence: 81%
“…This indicates that under different shade groups, the higher chlorophyll concentration and more pigment-binding proteins are associated with their photons collected by photosystem II per unit. The light-harvesting complex of photosystem II is mainly composed of chlorophyll b ( Wu, 2022 ). In contrast, the low PAR, photochemical efficiency, and lower chlorophyll concentration in no-shade control plants indicate that cold temperatures might disrupt the membrane permeability in the cell compartment of tea leaves exposed to low temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations